ESTIMATION CORRELATION OF BIOMECHANICAL PARAMETERS AND VAULT START VALUE IN MEN'S ARTISTIC GYMNASTICS - Almir Atiković,; Elvir Kazazović,; Edina Kamanješavić,; Amra Nožinović-Mujanović, (Sport Scientific And Practical Aspects, 2025)
The gymnastics vault is a apparatus characterised by a complex and very short movement which can be divided into seven important phases. The aim of our research was to determine correlation between vault start value and run-up velocity, first flight phase, table support, second flight phase. In the correlations matrix criteria variables from the Code of Points FIG MAG (2017-2020) effected a statistically significant postive correlation with two variables: run-up velocity on springboad and second flight phase, but negative correlation with two variables first flight phase and table support. We can conclude that there are no differences in values in relation to the two cycle Code of Points..